The macrophage polarization in Entamoeba histolytica infection modulation by the C fragment of the intermediate subunit of Gal/GalNAc-inhibitable lectin - Dong, Dai; Zhang, Yuhan; Li, Wenjie; Zhang, Hongze; Cheng, Xunjia; Feng, Meng (Frontiers in Immunology, 2024)
The protozoan parasite Entamoeba histolytica is the causative agent of amebiasis, with clinical outcomes ranging from asymptomatic infections to severe invasive diseases. The innate immune system, particularly macrophages, is of paramount importance in resisting the invasion of host tissues and organs by the trophozoites of E. histolytica. Parasite-derived pathogenic factors, such as lectins, play a pivotal role in the promotion of macrophage polarization phenotypes that have undergone alteration. Nevertheless, the precise mechanisms by which E. histolytica modulates immune polarization remain largely unknown. The current study focused on the immunomodulatory effects of the Igl-C fragment of E. histolytica Gal/GalNAc lectin on macrophage polarization. These results demonstrated that Igl-C could induce the secretion of IL-1β, IL-6, and other cytokines, activating a mixed M1/M2 polarization state. M1 polarization of macrophages occurs in the early stages and gradually transitions to M2 polarization in the later stages, which may contribute to the persistence of the infection. Igl-C induces the macrophage M1 phenotype and causes the release of immune effector molecules, including iNOS and cytokines, by activating the NF-κB p65 and JAK-STAT1 transcription factor signaling pathways. Furthermore, Igl-C supports the macrophage M2 phenotype via JAK-STAT3 and IL-4-STAT6 pathways, which activate arginase expression in later stages, contributing to the tissue regeneration and persistence of the parasite. The involvement of distinct signaling pathways in mediating this response highlights the complex interplay between the parasite and the host immune system. These findings enhance our understanding of the Igl-C-mediated pathogenic mechanisms during E. histolytica infection.